2020
DOI: 10.1039/d0ta08979f
|View full text |Cite|
|
Sign up to set email alerts
|

Dual-defect surface engineering of bimetallic sulfide nanotubes towards flexible asymmetric solid-state supercapacitors

Abstract: Nickel cobalt sulfide (NiCo2S4) has been known as a promising battery-type material for electrochemical energy storage. However, the slow kinetics of charge transfer and ion diffusion, as well as the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
98
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 157 publications
(100 citation statements)
references
References 70 publications
2
98
0
Order By: Relevance
“…The PXRD pattern showed that in comparison to the NiS 2 , the peaks of NCoSC electrode aremore intense, indicating the homogeneous distribution of Co in NiS 2 and NiCoS 2 . In addition to the above peaks, a small peak also appeared at 2θ ≈ 18 • , which corroborated well with the characteristic (111) plane of NiCo 2 S 4 [5,13,17]. A broad hump at 2θ ≈ 23 to 26 • was detected in the PXRD pattern of all the samples due to the (002) plane of coated carbon.…”
Section: Pxrd Pattern Analysissupporting
confidence: 79%
“…The PXRD pattern showed that in comparison to the NiS 2 , the peaks of NCoSC electrode aremore intense, indicating the homogeneous distribution of Co in NiS 2 and NiCoS 2 . In addition to the above peaks, a small peak also appeared at 2θ ≈ 18 • , which corroborated well with the characteristic (111) plane of NiCo 2 S 4 [5,13,17]. A broad hump at 2θ ≈ 23 to 26 • was detected in the PXRD pattern of all the samples due to the (002) plane of coated carbon.…”
Section: Pxrd Pattern Analysissupporting
confidence: 79%
“…The lowered capacitance at higher current densities is also attributed to the insufficient electrolyte ions diffusion kinetics across the micropores owing to the narrow pore size at higher operating current densities, the reduced accumulation amount of electrolyte ions onto porous electrode interface results in the decrement in specific capacitance 56 . The presence of dual hetero atoms such as O and P greatly reduces such resistance and increases the pore utilization to achieve a high capacitance 57 . The Ragone plot of the device in KOH electrolyte calculated from discharge curves at different current densities is displayed in Figure 4e.…”
Section: Please Do Not Adjust Marginsmentioning
confidence: 99%
“…Kang et al. [ 127 ] incorporated P dopant and created S vacancies on the surface of NiCo 2 S 4 nanotubes via anion exchange and phosphidation processes, which reduced oxidation states of Ni and Co active sites and improved electrical conductivity. Partial substitution of S with P also increased the covalent property of the derived electrode, which promoted charge transfer kinetics and enriched faradaic redox chemistry.…”
Section: Strategies For Improving Electrochemical Activity Of Tmcsmentioning
confidence: 99%